2020
DOI: 10.1016/j.jbmt.2020.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Role of fascial connectivity in musculoskeletal dysfunctions: A narrative review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 44 publications
(25 reference statements)
2
22
0
Order By: Relevance
“…Unfortunately, there is a dearth of such studies at present. Even though the levels of evidence in this review may be considered arbitrary, it seems unlikely that a different review approach or grading system would have resulted in a different conclusion (Ajimsha et al, 2020). Although efforts were made to gather most of the published studies, some relevant trials might have been missed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, there is a dearth of such studies at present. Even though the levels of evidence in this review may be considered arbitrary, it seems unlikely that a different review approach or grading system would have resulted in a different conclusion (Ajimsha et al, 2020). Although efforts were made to gather most of the published studies, some relevant trials might have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have found the role of fascia of interest and importance in musculoskeletal disorders, due to its potential to influence muscle activity and continuity. (Ajimsha et al, 2020). Studies have already demonstrated the role of fascia as a connecting link between the skeletal muscles throughout the body that are linked to each other by fascial tissue forming a network with some specific patterns (Luomala and Pihlman, 2016;Wilke et al, 2016a) that can undergo dysfunction and pain if under or over used (Ajimsha et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We further analysed the treatment effectiveness through determining change in symptom severity. Patients' symptom severity was classified as mild (0-15), moderate (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) or severe (>29) based on their total score (Table 4). Before the implementation of treatment, most patients had severe (42%) or moderate symptoms (45%).…”
Section: Impact Of Interventionmentioning
confidence: 99%